2015
DOI: 10.1093/molbev/msv006
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Resistance and Sensitivity Modulate Evolution of High-Level Resistance to Drug Combination Treatment in Staphylococcus aureus

Abstract: As drug-resistant pathogens continue to emerge, combination therapy will increasingly be relied upon to treat infections and to help combat further development of multidrug resistance. At present a dichotomy exists between clinical practice, which favors therapeutically synergistic combinations, and the scientific model emerging from in vitro experimental work, which maintains that this interaction provides greater selective pressure toward resistance development than other interaction types. We sought to exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 64 publications
5
100
0
Order By: Relevance
“…Several studies investigated the effects of antibiotic combinations with different drug interactions on spontaneous resistance evolution and revealed a general trend that antagonistic drug combinations lead to slower resistance evolution than synergistic ones [11,12]. However, recent work on S. aureus suggested that this trend may not hold generally when bacteria evolve higher levels of resistance as the drug interactions themselves might change due to resistance mutations [75].…”
Section: Drug Combinations That Minimize Resistance Evolutionmentioning
confidence: 99%
“…Several studies investigated the effects of antibiotic combinations with different drug interactions on spontaneous resistance evolution and revealed a general trend that antagonistic drug combinations lead to slower resistance evolution than synergistic ones [11,12]. However, recent work on S. aureus suggested that this trend may not hold generally when bacteria evolve higher levels of resistance as the drug interactions themselves might change due to resistance mutations [75].…”
Section: Drug Combinations That Minimize Resistance Evolutionmentioning
confidence: 99%
“…For consistency, stocks were revived from Days 0 (Ancestor), 5,10,15,19,20,25,30,35 During analysis of the mutations, we deduced that there were some cross-contaminations between replicates in a few lineages. Namely, we saw sets of mutations that were identical in 2 replicates.…”
Section: Adaptive Laboratory Evolutionmentioning
confidence: 99%
“…Collateral sensitivities between drugs have been used to design drug cycling strategies and to explain the decreased rate of adaptation to certain antibiotics [12,14,[18][19][20][21][22][23]. Drug deployment strategies that exploit such collateral sensitivities between pairs of antibiotics to minimize resistance evolution have been tested in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration that several specific rifampicin resistance mutations can prevent bacterial clearance by daptomycin in vitro can have potential clinical implication regarding the usage rifampicin and daptomycin in combination therapy. A deeper understanding of how evolution of microbial resistance towards a given antibiotic influences susceptibility or resistance to other drugs would have profound impact as it could be exploited to fight resistance rise through combination therapy or by the temporal cycling of different antibiotics [18, 64, 65]. …”
Section: Discussionmentioning
confidence: 99%
“…Because of their implications in central cell processes, such as DNA replication, translation, transcription and cell-wall metabolism regulation, mutations arising in these genes have been associated with a broad range of pleiotropic effects in addition to the antibiotic resistance that they cause [17]. An increasing body of literature shows that antibiotic resistance mutations can lead to broader negative therapeutic consequences through cross-resistance to other antimicrobials [1820], increased biofilm formation [21], increased virulence [2225] and enhanced immune evasion [2528]. However, there is currently no efficient method to identify pleiotropic mutations.…”
Section: Introductionmentioning
confidence: 99%